Noninvasive Detection of Extracellular pH in Human Benign and Malignant Liver Tumors Using CEST MRI - Tang, Yanyan; Xiao, Gang; Shen, Zhiwei; Zhuang, Caiyu; Xie, Yudan; Zhang, Xiaolei; Yang, Zhongxian; Guan, Jitian; Shen, Yuanyu; Chen, Yanzi; Lai, Lihua; Chen, Yuanfeng; et al. (Frontiers in Oncology, 2020)
Purpose In this study, we aimed to use 3T magnetic resonance imaging (MRI), which is clinically available, to determine the extracellular pH (pHe) of liver tumors and prospectively evaluate the ability of chemical exchange saturation transfer (CEST) MRI to distinguish between benign and malignant liver tumors. Methods Different radiofrequency irradiation schemes were assessed for ioversol-based pH measurements at 3T. CEST effects were quantified in vitro using the asymmetric magnetization transfer ratio (MTRasym) at 4.3 ppm from the corrected Z spectrum. Generalized ratiometric analysis was conducted by rationing resolved ioversol CEST effects at 4.3 ppm at a flip angle of 60 and 350°. Fifteen patients recently diagnosed with hepatic carcinoma and five patients diagnosed with hepatic hemangioma [1 male; mean age, 48.6 (range, 37–59) years] were assessed. Results By conducting dual-power CEST MRI, the pH of solutions was determined to be 6.0–7.2 at 3T in vitro. In vivo, ioversol signal intensities in the tumor region showed that the extracellular pH in hepatic carcinoma was acidic(mean ± standard deviation, 6.66 ± 0.19), whereas the extracellular pH was more physiologically neutral in hemangioma (mean ± standard deviation, 7.34 ± 0.09).The lesion size was similar between CEST pH MRI and T2-weighted imaging. Conclusion dual-power CEST MRI can detect extracellular pH in human liver tumors and can provide molecular-level diagnostic tools for differentiating benign and malignant liver tumors at 3T.